Classroom Management in Improving Elementary School Students' Learning Abilities - Jannah, Rauhun; Taufik, M. (JUPE : Jurnal Pendidikan Mandala, 2025)
Classroom management is a crucial factor in creating a conducive and effective learning environment. This study aims to analyze the role of classroom management in improving students' learning abilities in elementary schools. The research method used was descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The results indicate that good classroom management, including structuring the learning environment, managing time, and consistently implementing classroom rules, can improve student motivation, participation, and learning outcomes. Furthermore, teacher skills in creating positive interactions and controlling behavior also significantly influence the learning environment. Therefore, teachers' ability to manage the classroom is a key competency that needs to be developed to improve the quality of learning.